A Secondary Mixed Methods Analysis of a Pay-it-Forward Gonorrhea/Chlamydia Testing Program Among Men Who Have Sex With Men in China. Issue 6 (June 2020) - Li, Katherine T.; Huang, Wenting; Tang, Weiming; Wu, Feng; Zhao, Yang; Wu, Dan; Yang, Fan; Zhang, Tiange P.; Forastiere, Laura; Alexander, Marcus; Kumar, Navin; Tucker, Joseph D.
Abstract : Background: Gonorrhea and chlamydia are common among Chinese men who have sex with men (MSM), but testing rates are low. We developed a pay-it-forward program where men receive a free gonorrhea/chlamydia test and can then donate toward future participants' tests. This study aims to investigate drivers of testing uptake and donation using a mixed methods approach. Methods: We used a sequential explanatory design to explore drivers of testing uptake and donation unique to pay-it-forward through a quantitative cross-sectional survey and a qualitative thematic analysis of semistructured interviews. We collected data on sociodemographics and perceived benefits of pay-it-forward among men offered the pay-it-forward interventionand analyzed testing uptake and donations using descriptive statistics and logistic regression. We then conducted 30 semistructured interviews with men and coded interview data to identify themes. Results: Three hundred and one MSM were offered pay-it-forward and 55% (165/301) received gonorrhea/chlamydia testing. Ninety-one percent (150 of 165) donated any amount with a mean of 58.31 ± 53.39 RMB (US $8.61 ± 7.88), or 39% of the standard price of gonorrhea/chlamydia testing. Getting tested was not associated with income, but donations were higher in the highest income bracket (adjusted odds ratio, 7.12; 95% confidence interval, 1.61–31.52). Fifty-eight percent (94 of 162) selected "more MSM can get tested, " and 54% (88 of 162) selected "I can help someone else" as benefits of pay-it-forward. Qualitative themes for drivers of testing and donation included flexible pricing, generosity and reciprocity, and MSM community identity. Conclusions: Quantitative and qualitative results suggest that this pay-it-forward program may increase gonorrhea/chlamydia testing by reducing cost barriers, leveraging generosity and reciprocity, and mobilizing community altruism. Abstract : A mixed methods analysis found that drivers of a pay-it-forward gonorrhea/chlamydia testing program included flexible pricing, gift-giving and generosity, and community identity and collectivism.Supplemental digital content is available in the text.